Novel, divergent simian hemorrhagic fever viruses in a wild Ugandan red colobus monkey discovered using direct pyrosequencing. - Michael Lauck; David Hyeroba; Alex Tumukunde; Geoffrey Weny; Simon M Lank; Colin A Chapman; David H O'Connor; Thomas C Friedrich; Tony L Goldberg (PLoS ONE, 2011)
Simian hemorrhagic fever virus (SHFV) has caused lethal outbreaks of hemorrhagic disease in captive primates, but its distribution in wild primates has remained obscure. Here, we describe the discovery and genetic characterization by direct pyrosequencing of two novel, divergent SHFV variants co-infecting a single male red colobus monkey from Kibale National Park, Uganda.The viruses were detected directly from blood plasma using pyrosequencing, without prior virus isolation and with minimal PCR amplification. The two new SHFV variants, SHFV-krc1 and SHFV-krc2 are highly divergent from each other (51.9% nucleotide sequence identity) and from the SHFV type strain LVR 42-0/M6941 (52.0% and 51.8% nucleotide sequence identity, respectively) and demonstrate greater phylogenetic diversity within SHFV than has been documented within any other arterivirus. Both new variants nevertheless have the same 3' genomic architecture as the type strain, containing three open reading frames not present in the other arteriviruses.These results represent the first documentation of SHFV in a wild primate and confirm the unusual 3' genetic architecture of SHFV relative to the other arteriviruses. They also demonstrate a degree of evolutionary divergence within SHFV that is roughly equivalent to the degree of divergence between other arterivirus species. The presence of two such highly divergent SHFV variants co-infecting a single individual represents a degree of within-host viral diversity that exceeds what has previously been reported for any arterivirus. These results expand our knowledge of the natural history and diversity of the arteriviruses and underscore the importance of wild primates as reservoirs for novel pathogens.